Ответ:
Объяснение:
a) 46^2-2*46*31+31^2 = (46-31)^2 = 15^2 = 225
b)(37^2-23^2) / (47^2-13^2) = ((37-23)(37+23))/((47-13)(47+13))=(14*60)/(34*60) = 14/34
c)(26^3+17^3)/(26^2-26*17+17^2) = (26 + 17)(26^2 – 17*26 + 17^2)/(26^2-26*17+17^2)=26+17=43
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
a) 46^2-2*46*31+31^2 = (46-31)^2 = 15^2 = 225
b)(37^2-23^2) / (47^2-13^2) = ((37-23)(37+23))/((47-13)(47+13))=(14*60)/(34*60) = 14/34
c)(26^3+17^3)/(26^2-26*17+17^2) = (26 + 17)(26^2 – 17*26 + 17^2)/(26^2-26*17+17^2)=26+17=43